2020
DOI: 10.1002/hed.26215
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of personal protective equipment for head and neck cancer surgery during COVID‐19 pandemic

Abstract: Background: COVID-19 pandemic has led to a global shortage of personal protective equipment (PPE). This study aims to stratify face shield needs when performing head and neck cancer surgery. Methods: Fifteen patients underwent surgery between March 1, 2020 and April 9, 2020. Operative diagnosis and procedure; droplet count and distribution on face shields were documented.Results: Forty-five surgical procedures were performed for neck nodal metastatic carcinoma of unknown origin (n = 3); carcinoma of tonsil (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
0
10
0
2
Order By: Relevance
“…Although not a direct focus of this literature review, the stratification of PPE is worth mentioning before delving into the innovative solutions involving the creation of new PPE. Chow et al 29 found that droplet contamination was highest and most widespread during osteotomies, indicating that these types of surgeries warrant the most advanced PPE, while transoral robotic surgeries have the lowest risk of droplet contamination, suggesting that less stringent PPE is sufficient for providers during these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Although not a direct focus of this literature review, the stratification of PPE is worth mentioning before delving into the innovative solutions involving the creation of new PPE. Chow et al 29 found that droplet contamination was highest and most widespread during osteotomies, indicating that these types of surgeries warrant the most advanced PPE, while transoral robotic surgeries have the lowest risk of droplet contamination, suggesting that less stringent PPE is sufficient for providers during these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…It had anti-fog and anti-glare properties with no hearing restrictions. Each face shield was put against a white background with 12 grids measuring 7 cm × 7 cm each to facilitate counting at maximal magnification [ 11 ]. Each plastic sheet was carefully removed and placed against a white background for counting.…”
Section: Methodsmentioning
confidence: 99%
“…Disposable caps should be preferred-personal surgical caps should not be used; if used, they should be washed and disinfected after the case. [54] Disposable foot protector/overshoe and waterproof surgical overalls should be worn, especially in cases where fluid contamination is thought to be high. Then, the hands should be washed, and at least an N95 mask should be put on.…”
Section: Preoperative Preparation Of the Operation Roommentioning
confidence: 99%
“…In the end, all cutting tools should be collected in a container in accordance with surgical procedures. [54,55] Many devices used during operations create a "smoke" by burning tissue microparticles, creating combustion products, and carbon dioxide suspension with the risk of aerosolizing infectious diseases. These devices include electrocautery, ultrasonic harmonic devices and lasers used for tissue ablation.…”
Section: Protection Of the Patient And The Team During The Surgerymentioning
confidence: 99%